PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN KAIN TENUN DI DESA MASALILI KECAMATAN KUNTUNAGA KABUPATEN MUNA - Muchtar, Putriani; Kalimin, La Ode; Yusuf, Hayat (-)
The aim of this study; (1) To see decisions, influence. Purchasing decisions at Aneka Jaya Kendari Store (2) The effect of Sales Promotion decisions on purchasing decisions at Aneka Jaya Kendari Stores (3). The effect of personal selling decisions on purchasing decisions at Aneka Jaya Kendari Store (5) The effect of direct marketing on purchasing decisions at Aneka Jaya Kendari Stores. The sample in this study was maybe 50 people. The data method in this study is to use interviews and questionnaires. The method of analysis in this study uses multiple linear regression analysis. The results showed that: (1) Advertising (Advertising) had a significant effect on purchasing decisions; (2) Sales Promotion (Sales Promotion) has a significant effect on purchasing decisions; (3) Public Relations (Public Relations) has a significant effect on purchasing decisions; (4) Personal selling (salesperson) has a significant effect on purchasing decisions; (3) Direct Marketing (Direct Marketing) has a significant effect on purchasing decisions.Â